Assessment of the quality of life of organ reoipients based on the results of the First Russian transplant games - T. Yu. Shelekhova; E. E. Achkasov; I. A. Lazareva; Yu. A. Krumkacheva; A. A. Sungatulina; S. V. Gautier (Вестник трансплантологии и искусственных органов, 2023)
Objective: to evaluate the role of physical activity (at sports games) in improving the quality of life of organ recipients.Materials and methods. We examined 42 adult lung, heart, kidney and liver recipients, and patients undergoing renal replacement therapy (mean age 42.6 ± 12.09 years) - participants of the First Russian Transplant Games. The results were analyzed. Quality of life of the recipients was assessed using the nonspecific SF-36 questionnaire.Results. After solid organ transplantation, the interviewed recipients answered that they try to lead an active lifestyle, to engage in accessible physical activities, and to participate in sports events intended for organ recipients. Assessment of the quality of life according to the SF-36 questionnaire showed that all the participants had high scores in terms of the physical and psychological component, which is associated with regular physical training and sports. Conclusion. Physical exercise and active participation in sports activities are an important component in the socialization and rehabilitation of organ recipients. These two factors also improve the psychological and physical components of the quality of life of the recipients.